Research with undocumented migrant participants - René Leyva Flores; Miguel Valencia-Contrera; Jorge Cancino-Jiménez; Naldy Febré (Revista Cuidarte)
Globally, migration is increasing at an accelerated and sustained rate, driven by social, political, and economic factors that prompt the displacement of people across countries, resulting in significant migratory waves. It is estimated that there are 272 million international migrants worldwide3. Migration is defined by the International Organization for Migration (IOM) as the “Movement of persons away from their place of usual residence, either across an international border or within a State”.